2000
DOI: 10.3354/dao039201
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the electron-dense bodies of the PKX parasite, agent of proliferative kidney disease in salmonids

Abstract: Ultrastructural observations on structures associated with the 'haplosporosome'-like electron-dense bodies (EDBs) of the primary cell of the extrasporogonic stage of PKX are descr~bed. Observations made include formation of EDBs by the trans-Golgi network, an additional membrane associated with EDB structure, confronting cisternae, engulfment and presence of EDBs in multivesicular bodies, fusion of EDBs with the plasmalemma, degeneration of EDBs in disintegrating primary cells and endocytosis of PKX cytoplasm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 12 publications
1
32
0
Order By: Relevance
“…24 & 25 in Hine & Wesney 1992), and similar dense MVBs occur in the cytoplasm and are involved in haplosporogenesis in Haplosporidium nelsoni (Perkins 1968(Perkins , 1979. Although vegetative stages of the myxozoan parasite PKX also form bodies resembling haplosporosomes from the trans-Golgi face, and these bodies are seen in MVBs, the latter are formed when the bodies are engulfed by cup-like structures (Morris et al 2000), which were not observed here.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…24 & 25 in Hine & Wesney 1992), and similar dense MVBs occur in the cytoplasm and are involved in haplosporogenesis in Haplosporidium nelsoni (Perkins 1968(Perkins , 1979. Although vegetative stages of the myxozoan parasite PKX also form bodies resembling haplosporosomes from the trans-Golgi face, and these bodies are seen in MVBs, the latter are formed when the bodies are engulfed by cup-like structures (Morris et al 2000), which were not observed here.…”
Section: Discussionmentioning
confidence: 43%
“…In the haplosporidian Haplosporidium nelsoni, haplosporosomes align along the plasma membrane with an invagination in the internal membrane orientated at 90°to the surface (Scro & Ford 1990), and they disappear in the early stages of sporulation (Perkins 1968), supporting the interpretation that they may be involved in spore wall formation. The similar sporoplasmosomes of PKX, unlike the sporoplasmosomes of other myxozoans (Anderson et al 1999), have a lucent bar-like invagination and also orientate along the plasma membrane (Morris et al 2000). However, the PKX organism, Tetracapsula bryosalmonae, also has haplosporosomes (Canning et al 2000) which do not orientate along the plasma membrane, suggesting that they have an alternative function.…”
Section: Discussionmentioning
confidence: 99%
“…These appear to be fundamental differences, but they may not be. Haplosporosomes occur in haplosporidians (Haplosporidium, Minchinia, Bonamia, Urosporidium), paramyxeans (Paramyxa, Marteilia, Marteilioides), and the vegetative stages of myxozoans (Morris et al 2000). The latter are multicellular organisms, now regarded as cnidarians, and paramyxeans appear multicellular during sporulation.…”
Section: Parasite Taxonomic Affinitiesmentioning
confidence: 99%
“…However, they are ultrastructurally and developmentally very different, casting doubt on the phylogeny based on 1 gene sequence. Haplosporosomes also occur in the vegetative stages of some myxozoans (Morris et al 2000), which are bilaterians (Okamura et al 2002) not protists. Therefore, haplosporosomes are not by themselves of phylogenetic significance.…”
Section: Introductionmentioning
confidence: 99%